Knowledge, Attitude and Practice of Gynecologists and Midwifes toward Oral Health in Pregnant Women in Kerman (2016) - Tayebeh Malek Mohammadi; Mahsa Malek Mohammadi (Mashhad University of Medical Sciences, 2017)
Introduction: Pregnancy is an important period during which the pregnant mother should receive needed oral health education and related examinations. Researches have shown the association between oral health complications and unwanted outcomes of pregnancy such as preterm birth or low birth weight. Therefore, this study was performed with aim to assess the attitude, knowledge and practice of gynecologists and midwifes regarding pregnancy oral health care. Methods: This descriptive-analytic study was performed on 204 gynecologists and midwifes in Kerman in 2016. They were assessed using a validated self-administered questionnaire including demographic information and questions about knowledge, attitude and practice. Data analysis was conducted using SPSS software (version 21) and Chi-square, Mann Whitney and Pearson tests. Results: Mean score of knowledge among participants was 6.55±2.1 that no statistically significant difference was found between gynecologists and midwifes (P=0.903). About 165 of them (81%) stated that they referred their patients to the dentist and 174 (85.7%) referred those who needed to dental care to the dentist. There was no statistically significant difference between gynecologists' and midwifes' attitude (p>0/05). Conclusion: The findings showed that considering gynecologists' and midwifes' knowledge about importance of oral health during pregnancy, they had proper attitude and practice, but it still presents discrepancies with standard guidelines that indicates the need to upgrade their skill and knowledge in order to reach the best care for this period.